Inulin, a flexible oligosaccharide. II: Review of its pharmaceutical applications. (10th December 2015) - Mensink, Maarten A.; Frijlink, Henderik W.; van der Voort Maarschalk, Kees; Hinrichs, Wouter L.J.
Highlights: Inulin is a versatile carbohydrate with many diverse applications in pharma. A promising use of inulin is colon specific drug delivery. A promising use of inulin is stabilizing and adjuvating vaccine formulations. Abstract: Inulin is a flexible oligosaccharide which has been used primarily in food for decades. Recently new applications in the pharmaceutical arena were described. In a previous review (Mensink et al. (2015) . Carbohydrate Polymers, 130, 405) we described the physicochemical characteristics of inulin, characteristics which make inulin a highly versatile substance. Here, we review its pharmaceutical applications. Applications of inulin that are addressed are stabilization of proteins, modified drug delivery (dissolution rate enhancement and drug targeting), and lastly physiological and disease-modifying effects of inulin. Further uses of inulin include colon specific drug administration and stabilizing and adjuvating vaccine formulations. Overall, the uses of inulin in the pharmaceutical area are very diverse and research is still continuing, particularly with chemically modified inulins. It is therefore likely that even more applications will be found for this flexible oligosaccharide.